Enhancing extraction and purification of phycocyanin from Arthrospira sp. with lower energy consumption - Gorgich, Malihe (2021)
Phycocyanin is a light-blue water-soluble natural pigment with wide application in fields including pharmaceutical, cosmetic and food industry. Arthrospira platensis is considered a natural bio-factory for obtaining phycocyanin, and although suitable cultivation conditions can enhance the pigment content, the importance of extraction and purification should not be overlooked, because the chemicals used in those steps can affect the quality of phycocyanin. Further, changes in temperature, or approaches used to extract other protein types from biomass, have been reported to degrade phycocyanin, influencing its final quality, while also contributing to higher energy consumption in the extraction process. Hence, this work compares several approaches for phycocyanin extraction, and analyzed the effects of changes in operating conditions, such as exposure time, application of solvent buffer, and ultrasonication, on the extraction yield, the extracts purity, and the process energy use efficiency. Experimental results point to promising improvements in the extraction yield with high purity of phycocyanin (44.24 mg/g with purity ratio of 0.34), when suitable operating parameters were used (2 h exposure to potassium phosphate buffer with 20 min of ultrasonication).